Copper and ceruloplasmin concentrations in the blood serum oe schizophrenic patients - Luis Marques-Assis; Francisco Bastos De Jorge (Arquivos de Neuro-Psiquiatria)
The serum copper (26 cases) and ceruloplasmin (20 cases) are studied in 45 patients with schizophrenia. The following conclusions were drawn from this study: 1) the blood copper is significantly higher in patients with schizophrenia; 2) the variations of ceruloplasmin are not significant. The slightly amounts of copper in schizophrenia may have not a diagnostic value.